2017
DOI: 10.1016/j.ypmed.2017.08.004
|View full text |Cite
|
Sign up to set email alerts
|

Prostate-specific antigen screening: An update of physician beliefs and practices

Abstract: PSA testing for early detection of prostate cancer decreased dramatically following the 2012 PSA screening recommendation against routine screening of asymptomatic men. In an assessment of the screening behaviors of primary care providers, the majority (61%) of family medicine and internal medicine practitioners who responded to a 2016 DocStyles online survey (608 of 1003) recommended prostate-specific antigen (PSA) testing based on individual risk or other factors, rather than routinely screening all men for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 14 publications
1
7
0
Order By: Relevance
“…About 39% of PCPs and 40% of NPs had been practicing medicine for 11-20 years, and 31% of PCPs and 23% of NPs were long-term practitioners of > 20 years. Demographic characteristics of PCPs are similar to that recently reported by Hall et al [10].…”
Section: Resultssupporting
confidence: 84%
“…About 39% of PCPs and 40% of NPs had been practicing medicine for 11-20 years, and 31% of PCPs and 23% of NPs were long-term practitioners of > 20 years. Demographic characteristics of PCPs are similar to that recently reported by Hall et al [10].…”
Section: Resultssupporting
confidence: 84%
“…In our study, answers to the question concerning the proportion of men aged ≥45 years that received (at least) one PSA test varied widely, whereas the frequency of ordering PSA tests among GPs in Sweden showed moderate variation (25). Compared with primary care physicians in the US, physicians in our study were more proactive in recommending a PSA test (24). One-quarter of physicians in the US study routinely offered and recommended a PSA test to all asymptomatic male patients of screening age, regardless of whether the patient asked about the test.…”
Section: Discussionmentioning
confidence: 57%
“…In contrast, about one-fifth of the GPs in our study supported this assumption. However, a US-based study showed that three-quarters of the primary care physicians surveyed strongly disagreed, disagreed, or were undecided as to whether the PSA test extended life (24). This may be due, in part, to the results of a systematic review, concluding that at best, PCa screening leads to a small reduction in disease-specific mortality over 10 years but has no effect on overall mortality (9).…”
Section: Discussionmentioning
confidence: 99%
“…The reason for the exclusion of full texts was mainly that the results were unrelated to the aim of the study. Finally, 14 studies met the inclusion criteria (11,(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33).…”
Section: Literature Searchmentioning
confidence: 99%
“…All articles were cross-sectional, and 7 of them (50%) were published between 2015 and 2017. Most of them were carried out in the USA (5, 35.7%) (21,23,25,29,31), 2 (14.3%) in Spain (24, 26), and the rest in countries such as Malaysia (22), Saudi Arabia (27), Netherlands (28), South Africa (30), Caribbean (32), Switzerland (33), and Germany (11) (Table 1).…”
Section: Characteristics Of Identified Studiesmentioning
confidence: 99%